Diversity and abundance of mud crabs (Scylla spp.) living in mangrove forest ecosystems on Serangan Island, Bali, Indonesia - IDA BAGUS JELANTIK SWASTA; IDA AYU AMARILIA DEWI MURNI; JASMINE MASYTHA AMELIA (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Swasta IBJ, Murni IAAD, Amelia JM. 2023. Diversity and abundance of mud crabs (Scylla spp.) living in mangrove forest ecosystems on Serangan Island, Bali. Biodiversitas 24: 5664-5670. The mangrove forest ecosystem on Serangan Island contains dozens of types of aquatic fauna, including mud crabs from the Scylla genus (Scylla spp). The objectives of this study were to obtain the variety and abundance of mud crabs and to determine the variety and abundance of mangroves on Serangan Island after the reclamation. This study's results are expected to make all parties aware of the ecological impact of reclamation activities on the coast. Data on mangrove diversity was collected through observation during a field survey. At the same time, samples of mud crabs were caught randomly using traps (rakang) of as many as 20 units set proportionally around Serangan Island. The fishing gear (rakang) is placed in the afternoon at 18.00, then taken in the morning at 06.00 to see the trapped mud crabs. The data on the diversity and abundance of mud crabs were processed to obtain a diversity index using the diversity index formula (H') from Shannon Wiener and quantitative and qualitative descriptive. The results showed that there are three types of mud crabs around Serangan Island, namely Scylla serrata (47.8%), Scylla olivacea (30.4%), and Scylla tranquebarica (21.8%) with a diversity index (H' ) of mud crabs was 1,047. Scylla serrata has the highest prevalence of 35%, followed by Scylla olivacea (25%) and Scylla tranquebarica (10%). The mangrove community on Serangan Island consists of 6 species, namely Rhizophora apiculate, Rhizophora stylosa, Ceriop tagal, Sonneratia alba, Avicennia lanata, and Brugierra gymnorhiza.